Teacher morale in the Zamboanga City High School its relationship to certain variables and implications for educational administration - Guevara, Pilar (Diaz) 1930- (s.n.], 1974)
The purpose of the study is to determine the morale status of the teachers of the Zamboanga City High School during the first few months of school year 1973-1974 and to relate this to some variables - age, salary, length of service, performance rating, group size, civil status, civil service status, educational qualification, and geographical location. The study also tries to determine the positive and negative morale tendencies and to draw implications for educational administration.